Between ASEAN demos and ASEAN kratos: the genesis of ASEAN public spheres - Abdul Muein Abadi (School of History, Politics and Strategic Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
This study centers on the following question: do the political, civil society organizations, and media infrastructure conditions exist for the emergence of ASEAN public spheres? The following definition of ASEAN public sphere have been constructed: a transnational site of deliberation in which civil society organizations reach an understanding about issues of common concern in ASEAN according to the norms of publicity. Patterns from three distinct structures that converged to form ASEAN public spheres has been identified. Firstly, the prime site of ASEAN’s governance consisting of the ASEAN Summit, ASEAN Community Councils, and ASEAN Secretariat has, to a certain extent, become open to the people’s input. Secondly, the emergence of transnational civil society and discursive publics in ASEAN. As a reservoir for the grassroot opinion- and will-formation, the civil society in ASEAN has been indispensable in terms of its norms of publicity and political efficacy. Thirdly, the cross borders communicative infrastructure has proven to be significant in terms of the grassroot formation fora as well as the mobilization of free and critical public opinion towards ASEAN across the region. They also challenge the “manipulative” and “manufactured consent” that tends to be propagated by the mainstream pro-political authority and pro-market media. Despite the prevailing supremacy of ASEAN’s political elites, as well as the interstate ICT cleavages in the region, I argue that a conducive milieu has developed in which ASEAN public spheres can indeed emerge.